2020
DOI: 10.1111/bjd.19644
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological changes in cutaneous lymphomas: an analysis of 8593 patients from the French Cutaneous Lymphoma Registry*

Abstract: Summary Background Primary cutaneous lymphomas (PCLs) are a heterogeneous group of T‐cell (CTCL) and B‐cell (CBCL) malignancies. Little is known about their epidemiology at initial presentation in Europe and about potential changes over time. Objectives The aim of this retrospective study was to analyse the frequency of PCLs in the French Cutaneous Lymphoma Registry (GFELC) and to describe the demography of patients. Methods Patients with a centrally validated diagnosis of primary PCL, diagnosed between 2005 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
2
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 28 publications
(67 reference statements)
3
40
2
15
Order By: Relevance
“…In contrast, studies from the USA based on much larger groups of patients (range 4310–6230) reported a prevalence of 0·64–0·87/100 000 population 4,5 . Therefore, based on the results of these latter studies and the current paper by Dobos et al ., 1 a similar prevalence of CL of around 0·90/100 000 population seems most likely in both Europe and the USA.…”
contrasting
confidence: 38%
See 3 more Smart Citations
“…In contrast, studies from the USA based on much larger groups of patients (range 4310–6230) reported a prevalence of 0·64–0·87/100 000 population 4,5 . Therefore, based on the results of these latter studies and the current paper by Dobos et al ., 1 a similar prevalence of CL of around 0·90/100 000 population seems most likely in both Europe and the USA.…”
contrasting
confidence: 38%
“…In this issue of the BJD , Dobos et al . present a retrospective analysis of epidemiological data from the French Cutaneous Lymphoma Registry (FCLR) 1 . Based on 779 patients included in 2018 by the FCLR, the authors report an incidence of CL of 0·96 per 100 000 population.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Primary cutaneous T-cell lymphomas (CTCLs) vary in form from those of a very indolent type to extremely aggressive malignancies with bad prognosis. CTCLs are rare diseases with an annual incidence of around seven cases per million population [1]. The most common CTCLs are mycosis fungoides (MF) and Sézary syndrome (SS), which account for around 50% of all primary CTCLs [2,3].…”
Section: Cutaneous T-cell Lymphoma: Description Of the Main Entitiesmentioning
confidence: 99%